Identificação do Perfil Dermatoglífico e Somatotípico dos Atletas de Voleibol Masculino Adulto, Juvenil e Infanto-Juvenil, de Alto Rendimento no Brasil - Fidalgo Zary, J. C.; Fernandez Filho, J. (Revista Brasileira de Ciência e Movimento, 2007)
The present study focuses on the characteristics of the dermatoglyphic and somatotype profiles of high performance, male, volleyball young and adult athletes in Brazil. In elaborating this work, 11 athletes from the Brazilian Young Volleyball Team in the year 2003, 12 athletes of the Brazilian adult team in 2004 were observed. The practical implication in identifying the profile of volleyball players in Brazil, is incorporated with the needs of this sport modality. In Brazil, there are some datum in respect of the dermatoglyphic and somatotype aspects of the high performance athletes made by Fernandes Filho (1997) and Medina (2000). The groups were submitted to an evaluation to identify the dermatoglyphic profile by means of digital impressions (DI), following the protocol of Cummins and Midlo (1942), and also to an evaluation of somatotype, by the anthropometric method of Heath-Carter (1967). In identifying the genetic profile, the characteristics of models of the Digital Impressions were elaborated for high performance, male, young volleyball athletes, that included the most informative and integral indices: D10 = 11,91 ± 3,56; TRC = 116 ± 44,81; L = 6,82 ± 2,99; W = 2,55 ± 2,95 e A = 0,64 ± 1,50, showing high incidence of Loop (L) and low incidence of Arch (A). The predominant types of digital form were also established: W>L = 27,27 %; L>W = 18,18 %, 10L = 27,27 % e ALW = 27,27 %. In identifying the somatotype profile, the characteristics of the adult group studied were presented following the three components of somatotype of Heath-Carter, which were: endomorphy = 1,7 ± 0,32; mesomorphy = 3,8 ± 0,86; and ectomorphy = 3,9 ± 0,64. These values characterize the group studied as ectomesomorphyc. In adult team, we found D10 = 13,5 ± 2,88; TRC = 132,08 ± 38,27; L = 5,83 ± 2,21; W = 3,83 ± 2,44 e A = 0,33 ± 0,78, showing again high incidence of loops and low of archs. The predominant types of digital form were also established: W>L = 25 %; L>W = 25 % W = L = 25 %, 10L = 8,33 %, ALW = 8,33 e AL = 8,33 %. In identifying the somatotype profile, the characteristics of the group studied were presented following the three components of somatotype of Heath-Carter, which were: endomorphy = 2,6 ± 0,69; mesomorphy = 4,2 ± 1,69; and ectomorphy = 2,6 ± 0,69. These values characterize the group studied as equilibrated mesomorphy.